The Effect of Lpg Pipe Temperature on Product Weight Variation in Portable Gas Production Process - Endro Wibowo, Fogot; Surawan, Tri; Kurniawati, Nani; Digdoyo, Aji; Yulianto, Rudy (Devotion : Journal of Research and Community Service, 2025)
This study aims to analyze the effect of LPG pipe temperature on product weight variation in the portable gas production process. Variations in product weight often occur due to temperature fluctuations in the pipes that transfer LPG from storage tanks to gas cartridges. High temperatures caused by direct sunlight exposure alter the liquid–gas phase ratio of LPG, thus affecting its volume and final product weight. The research employed an experimental method by measuring pipe temperature at six different points and five time intervals (08:00, 10:00, 12:00, 14:00, and 16:00). The results showed that the highest pipe temperature occurred at 12:00 with an average of 40.15°C, correlating with product weight deviation beyond the standard (330±3 grams). A corrective action was implemented by insulating (jacketing) the LPG pipes to reduce heat exposure. After insulation, all measured products met the standard weight requirement. In conclusion, thermal protection of LPG pipes plays a significant role in maintaining product weight stability and improving the efficiency of the portable gas production process.